Pertumbuhan dan Hasil Tanaman Selada (Lactuca Sativa L.) pada Berbagai Konsentrasi Nutrisi AB Mix dengan Sistem Hidroponik Nutrient Film Technique (NFT) - Yolla Novia; Chairil Ezward; Seprido Seprido (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2023)
Lettuce is a leaf vegetable that is popular with the public. The increase and potential of lettuce cultivation requires efficient cultivation techniques. The production of a plant with a hydroponic system is closely related to the availability of a nutrient solution. This study aims to determine the growth response and yield of lettuce plants at various concentrations of AB-Mix nutrients with the NFT system. The design used in this study was a non-factorial completely randomized design (CRD) consisting of one factor, namely AB-Mix nutrition with 4 treatment levels, namely: K1 (850 ppm), K2 (1,050 ppm), K3 (1,250 ppm), K4 (1,450 ppm). Based on the results of the study, giving AB-Mix nutrient concentrations had a significant effect on the best plant height parameters with K4 treatment (1,450 ppm) with height (28.18 cm), number of leaves (9.61 strands), plant weight (43.47 grams), and consumption weight (38.27 grams).